2022
DOI: 10.3390/ijerph19042350
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Leisure-Time Physical Activity and Resistance Training on Nonalcoholic Fatty Liver Disease: A Nationwide Cross-Sectional Study

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease. The present study aimed to investigate the association of NAFLD with leisure-time physical activity (PA) levels and resistance training (RT). Methods: We used data from large nationwide cohorts in Korea. NAFLD was defined based on the Framingham steatosis index. Participants were categorized into four groups based on RT frequency and adherence to PA guidelines (≥150 min/week of moderate-intensity PA): Low-PA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, our study shows that among individuals with NAFLD, the risk for significant fibrosis decreases with more time spent in MVPA, TLAC. These data corroborate previous findings based on self-reports that physical activity was inversely associated with NAFLD and associated significant fibrosis [ 8 ], and higher intensities of physical activity showed larger protective effects [ 43 45 ]. Additionally, our predictive models quantify the relationship between the time engaged in MVPA, thereby, providing foundational data to better investigate these relationships in larger datasets that included both objective and self-reported measures of physical activity.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our study shows that among individuals with NAFLD, the risk for significant fibrosis decreases with more time spent in MVPA, TLAC. These data corroborate previous findings based on self-reports that physical activity was inversely associated with NAFLD and associated significant fibrosis [ 8 ], and higher intensities of physical activity showed larger protective effects [ 43 45 ]. Additionally, our predictive models quantify the relationship between the time engaged in MVPA, thereby, providing foundational data to better investigate these relationships in larger datasets that included both objective and self-reported measures of physical activity.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, they showed that total PA, measured by accelerometers over a 7-day period, were associated with lower all-cause and cardiovascular mortality in participants with NAFLD from NHANES 2003–2006 ( 26 ). In addition, several recent studies have demonstrated the inverse associations of PA with NAFLD prevalence based on different populations ( 11 13 ). Specially, Park, et al found that resistance training (characterized by muscle contraction against external resistance) combined with PA was relatively effective in reducing the risk of NAFLD ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several recent studies have demonstrated the inverse associations of PA with NAFLD prevalence based on different populations (11)(12)(13). Specially, Park, et al found that resistance training (characterized by muscle contraction against external resistance) combined with PA was relatively effective in reducing the risk of NAFLD (13). Chun, et al observed that PA had a protective effect against fibrosis, sarcopenia, and CVD in NAFLD (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schneider et al pointed out that increased PA is related to a decrease in NAFLD, even independent of adiposity [17]. Park et al recently added that, in addition to regular PA practice, resistance training and high levels of PA decreases the risk of NAFLD [18]. Although there are more studies assessing these relationships, studies reporting the relationship between different PA parameters and NAFLD are still scarce.…”
Section: Introductionmentioning
confidence: 99%